Fertility Characteristics and Contraceptive Use of the Married Women Working at Turgut Özal Medical Center - Karaoglu, Leyla; Cetin, Feray; Ilgar, Mehtap; Tekiner, Selda; Gunes, Gulsen; F. Genc, Metin; Egri, Mucahit; Pehlivan, Erkan (Annals of Medical Research, 2021)
None